Eksplorasi Etnomatematika dalam Permainan Tradisional Bekel Suku Sasak : (Studi Kasus pada Pembelajaran Matematika di Madrasah Tsanawiyah Swasta, Lombok) - Murni, Silvia; Pardi, M Habib Husnial; Evendi, Erpin (Mathematic Education Departement, State Islamic University of Mataram, 2025)
This study aims to determine the concept of mathematics, cultural values contained in the Sasak tribe's bekel game, and find out how the bekel game can be used in learning mathematics. This research uses a qualitative approach with the type of case study, data collection techniques through observation, interview guidelines, documentation, and questionnaires. The subjects in this study were MTs students who played bekel. The results showed that there are mathematical concepts in the game such as the concept of chance, building space in the form of a ball, and there are cultural values in the game such as the value of fun, the value of honesty, the value of democracy, and the value of aesthetics.